2015
DOI: 10.3390/su7078051
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Toolkit and a One-Day Teacher Education Workshop on ESD Teaching Content and Methods—A Study from Kosovo

Abstract: Environmental education in Kosovo is currently under reform. The new strategy for sustainable development demands a strong focus on education for sustainability in schools. However, a lack of teacher education might impede new approaches in the classroom. This study investigated how teachers in Kosovo approach locally-relevant environmental issues in the classroom before and after a one-day in-service workshop on teaching approaches related to education for sustainable development (ESD). Data were gathered in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 29 publications
0
12
0
1
Order By: Relevance
“…Outcomes: Most of the program evaluations included in the articles demonstrated or claimed positive effects on student/teacher learning related to ESD. Among these, five studies focused on teaching and learning assessment of ESD demonstrated a statistically significant effect [22,27,32,35,36], while three other studies focused on teacher education in the areas of ESD demonstrated the same [29,33,37]. For instance, some of these studies found that ESD courses strongly impacted participants' positive beliefs, norms and attitudes towards sustainable development [29,37].…”
Section: Strengths and Weaknesses Of Assessment Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…Outcomes: Most of the program evaluations included in the articles demonstrated or claimed positive effects on student/teacher learning related to ESD. Among these, five studies focused on teaching and learning assessment of ESD demonstrated a statistically significant effect [22,27,32,35,36], while three other studies focused on teacher education in the areas of ESD demonstrated the same [29,33,37]. For instance, some of these studies found that ESD courses strongly impacted participants' positive beliefs, norms and attitudes towards sustainable development [29,37].…”
Section: Strengths and Weaknesses Of Assessment Approachesmentioning
confidence: 99%
“…Studies also reported other challenges and constraints which affected the implementation of sustainable development education programs, initiatives, and goals. Pre-service teacher education that prioritizes ESD, ongoing in-service teacher training and support related to the practical use of ESD tools, in addition to teachers' perceptions of the feasibility of implementing ESD into lesson times, may influence the implementation of ESD [24,33]. In one study, the amount of time and school support necessary to integrate new teaching methods and content related to ESD hindered teachers' implementation of an ESD toolkit [33].…”
Section: Strengths and Weaknesses Of Assessment Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…From these, we selected 16 journals with 24 articles to be analyzed in detail (Table 1). [98] In the analysis, we followed the method of qualitative content analysis [99][100][101][102]. Inductive content analysis was used to analyze teaching methods, learning environments and features of useful teaching methods and implications [99,101].…”
Section: Methodsmentioning
confidence: 99%
“…For example, the environmental and the financial crisis is a mixture of finance and economy as well as of climate, resources and the environment. Sustainability education has to deal with ideology, social change, and political power relations, and could gain much from political science [98].…”
Section: Separate Disciplines and Split Curricula Complicates The Impmentioning
confidence: 99%